Biomass Chars: Elaboration, Characterization and Applications - Mejdi Jeguirim (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Thermochemical conversion processes convert biomass into gaseous, liquid and solid products named, syngas, bio-oil and char, respectively. Syngas and bio-oil are considered as alternative biofuels to fossil fuels and wide investigations are implemented currently on their production, purification, modification, and applications. Biomass chars have receiving an increasing attention since they lead to carbon sequestration, reduction of the amount of carbon rejected into the atmosphere and represent an friendly carbon source for numerous applications. In particular, biomass chars could be an efficient materials for energy production, syngas production and upgrading, water and air pollutants removal, soil amendment, fuel cells and supercapacitors development, and gas storage. Improving the knowledge of biomass chars elaboration techniques such as pyrolysis, gasification and hydrothermal carbonization is essential to determine the optimal production strategies for their economic viability. Furthermore, the characterization of the physicochemical, textural, structural and surface chemistry properties of the derived chars guide the selection of the suitable recovery processes in order to maximize their utility and therefore the benefits for the environment as well as for industries and agriculture.